Bibliometric analysis of research topics on blood–brain barrier breakdown and cognitive function over the last two decades (2000–2021) - Zhang, Ruirui; Zhang, Yiqi; Wu, Tong; Tian, Weitian; Luo, Jiamei; Shi, Yumiao; Su, Diansan; Shu, Huigang; Tian, Jie (Frontiers in Aging Neuroscience, 2023)
This study aimed to categorize and summarize research topics on the correlation between blood–brain barrier (BBB) breakdown and its effects on cognitive function. Bibliometric analysis methods were used to quantitatively and qualitatively assess research progress and predict future research hotspots. Relevant publications from the Web of the Science Core Collection were extracted on November 5, 2022 and analyzed to predict trends and hotspots in the field. We identified 5581 articles published from 2000 to 2021 about the BBB and cognition. The number of manuscripts on this topic increased steadily during this time period, especially after 2013. We found that the number of articles published in China increased gradually and is in second place behind the United States of America (USA). In the research field of BBB breakdown and cognitive function, the USA is still far ahead. Keyword burst detection suggested that cognitive impairment, neurodegeneration disease and neuroinflammation are emerging research hotspots. The mechanisms of BBB integrity breakdown and its effects on the deterioration of cognitive function are complex, and clinical treatment of the affected diseases has been a hot topic in the field over the past 22 years. Looking forward, this body of research is aimed at improving or maintaining patients’ cognitive abilities, by finding preventive measures and to provide a basis for finding new treatments of cognitive disorders.